PENERIMAAN PESERTA DIDIK BARU SISTEM ZONASI - Miftahussa Adah; Abubakar Umar; Yadi Fahmi Arifudin (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Education is one of the main pillars in the development of a country. To achieve quality and equitable education for all citizens, the acceptance of new students is very crucial. However, in practice, there are various problems that arise, especially related to injustice in access and educational opportunities. To overcome this challenge, the zoning system for accepting new students is one of the solutions introduced by many countries. This zoning concept aims to create fairness and openness in education by allocating students based on the geographical location where they live. One of the main benefits of the zoning system is educational equity. By distributing students evenly in various regions, diversity and equality will be created in the learning environment. This will help reduce social and economic disparities between regions, so that every child has the same opportunity to get access to a proper education. In addition, the zoning system also encourages inclusivity in education. By combining students from various social and cultural backgrounds, a multicultural learning environment will be formed. This can increase understanding, tolerance and mutual respect among students, thereby creating a generation that is more open and accepting of differences. However, it must be acknowledged that the implementation of the zoning system also faces its own challenges. One of the main problems is the limited capacity of schools in each region. If an area has a population of students that is more than the capacity of the existing schools, this can lead to accumulation and a decrease in the quality of education. Therefore, careful planning and management is needed so that the zoning system can run effectively. In addition, another challenge is the role of parents in supporting the implementation of the zoning system. Some parents may prefer schools in certain areas that are considered more prestigious than schools closer to where they live. This can lead to a shift in the problem from geographic disparities to social and educational inequalities. In order to overcome these obstacles, the government needs to provide adequate educational facilities and infrastructure, improve the quality of teaching staff, and involve all stakeholders in planning and evaluating the zoning system. Overall, the zoning system in accepting new students is a positive step towards a more inclusive and equitable education. By providing equal opportunities for every child to get access to quality education, the hope for a generation that is competitive and has a strong personality is increasingly real.